Assessment and treatment of vocabulary deficits in a multilingual child with SLI - Kambanaros, Maria; Grohmann, Kleanthes K. (My University, 2018)
Background: There is not much research on assessing and treating vocabulary deficits in multilingual children with SLI. Aim/s: To report on (i) expressive vocabulary deficits in the three languages of a multilingual school-aged child with specific language impairment (SLI); and (ii) whether cognates-words that share similar phonological information and identical meaning across languages (e.g., camel/καμήλα/ камила) could be used as a vocabulary learning strategy by exploiting the phonological information in the one language as a mechanism for language (phonological) transfer to the other (untrained) languages. Method: The participant (IS) had acquired Bulgarian (mother’s language) and Cypriot Greek (father’s language) from birth and was exposed to English (immersion schooling) and Standard Modern Greek (classroom instruction) on a daily basis for five years. She was assessed using an equivalent-based measure of expressive vocabulary common to her three languages on three separate occasions for each language, 10 days apart and later trained over a one-month period on 20 non-identical triple cognates that shared meaning and phonological features in the proficient language only, English, using a picture-based naming task. Results: Although comprehension of the target words in each language (Bulgarian, English, Greek) was normal, the results revealed a marked naming deficit across languages. Cognate therapy was provided in English by the school’s special education teacher after training. IS received phonological intervention only using a cueing hierarchy technique. Cross-linguistic transfer effects were evident during and after therapy, and were maintained one month post intervention. Generalisation to nontreatment words was evident especially for English during and post intervention. Conclusion: Attention to cognates for multilingual children with developmental language impairment is a topic ripe for further investigation.
Keywords: Specific language impairment; Multilingual; Child